Orientational Disorder in Adamantane and Adamantanecarboxylic Acid. Issue 5 (7th February 2017) - Beake, Edward O. R.; Tucker, Matthew G.; Dove, Martin T.; Phillips, Anthony E.
Abstract: The molecular crystals adamantane, C10 H16, and adamantanecarboxylic acid, C10 H15 COOH, undergo order–disorder phase transitions at 208 and 250 K, respectively. Reverse Monte Carlo refinement of total neutron scattering data collected from deuterated samples immediately above these phase transitions shows that the high‐temperature phases are well described by models in which the adamantyl groups are disordered over two sites. No correlation between the orientations of neighbouring molecules is observed. These results demonstrate that the intermolecular potential energy of these materials depends strongly on the orientation of the reference molecule but only very weakly on the orientations of its neighbours. Abstract : Short‐sighted : Total neutron scattering data reveal no correlation between the orientations of neighbouring molecules in the disordered phases of adamantane or adamantanecarboxylic acid. Despite the high molecular symmetry, reverse Monte Carlo refinement from initially random molecular orientations shows that these orientations in both materials follow a strongly bimodal distribution (shown for adamantane in figure).